METAPHYSICS IN THE BHAGAVAD GITA COMPARED WITH THE WESTERN PHILOSOPHIES: A HERMENEUTIC GAZE - Ghimire, Janardan (Researcher: A Research Journal of Culture and Society, 2018)
This article is an outcome of hermeneutical research carried out on the Bhagavad Gita, a core eastern text of Vedic philosophy. The main purpose of this article is to explore philosophical insights embedded in this historical scripture and help the readers to gain its greater understanding and insights. It also searches metaphysical principles consisted in the Bhagavad Gita and provides answer of the questions: what metaphysical principles can be seen in the Bhagavad Gita? How can it be interpreted? How the metaphysical principles of the Bhagavad Gita associates/disassociates with western theories of philosophy? Considering the questions, the Bhagavad Gita provides theory of creation, cycle of creation and destruction and discusses about Brahma element that is seed of creative principles, Atma, Paramatta, the God. It also includes theory of being (existence). In comparison with western philosophy, it comprises wider and in-depth metaphysical principles. In order to interpret metaphysical principles, this article elaborates general introduction of the Bhagavad Gita, general concept of metaphysics and metaphysical principle can be seen in the Bhagavad Gita. It also searches associations/ disassociations of metaphysical principles of the Bhagavad Gita with metaphysics of western schools of thought. Finally, it draws implication and conclusion. Researcher: A Research Journal of Culture and Society Vol. 3, No. 3, January 2018, Page: 33-46